Planetarium pedagogy and learning experience: exploration into planetarium education program / Mohammad Mubarrak Mohd Yusof … [et al.] - Mohd Yusof, Mohammad Mubarrak; Alias, Nurul Hidayah; Luaran, Johan Eddy; Syed Aris, Sharipah Ruzaina; Zulkipli, Zulinda Ayu (UiTM Press, 2022)
This paper is an exploration of the education program conducted by National Planetarium Kuala Lumpur (PNKL), educational theories well as the inclination of education program with the Standard Based Curriculum for Secondary School (KSSM) for science subject. The methods used in this study are document analysis and participant observation. This study has found that there are two types of education programs conducted by PNKL which are on-site program and off-site program. The Educational theories applied in the education programs are constructivism and behaviourism. Some educational approaches embedded via the education programs conducted by the PNKL are object-based learning and artful learning. The study also investigated the link between the education program with the Standard Based Curriculum for Secondary School in the science subject. The topics are best taught in the planetarium because of its capacity to speed up learning and help explain unobservable phenomena. The implications of this study and recommendations for future research are discussed based on the findings of the study.